The emerging role of E3 ubiquitin ligase RNF213 as an antimicrobial host determinant - Zhang, Yulu; Yuan, Yupei; Jiang, Lu; Liu, Yihan; Zhang, Leiliang (Frontiers in Cellular and Infection Microbiology, 2023)
Ring finger protein 213 (RNF213) is a large E3 ubiquitin ligase with a molecular weight of 591 kDa that is associated with moyamoya disease, a rare cerebrovascular disease. It is located in the cytosol and perinuclear space. Missense mutations in this gene have been found to be more prevalent in patients with moyamoya disease compared with that in healthy individuals. Understanding the molecular function of RNF213 could provide insights into moyamoya disease. RNF213 contains a C3HC4-type RING finger domain with an E3 ubiquitin ligase domain and six AAA+ adenosine triphosphatase (ATPase) domains. It is the only known protein with both AAA+ ATPase and ubiquitin ligase activities. Recent studies have highlighted the role of RNF213 in fighting against microbial infections, including viruses, parasites, bacteria, and chlamydiae. This review aims to summarize the recent research progress on the mechanisms of RNF213 in pathogenic infections, which will aid researchers in understanding the antimicrobial role of RNF213.